Enhanced biocompatibility of TiO2 surfaces by highly reactive plasma. (12th May 2016) - Junkar, Ita; Kulkarni, Mukta; Drašler, Barbara; Rugelj, Neža; Recek, Nina; Drobne, Damjana; Kovač, Janez; Humpolicek, Petr; Iglič, Aleš; Mozetič, Miran
Abstract: In the present study the biological response to various nanotopographic features after gaseous plasma treatment were studied. The usefulness of nanostructured surfaces for implantable materials has already been acknowledged, while less is known on the combined effect of nanostructured plasma modified surfaces. In the present work the influence of oxygen plasma treatment on nanostructured titanium oxide (TiO2 ) surfaces was studied. Characterization of the TiO2 surface chemical composition and morphological features was analyzed after plasma modification by x-ray photoelectron spectroscopy and by scanning electron microscopy while surface wettability was studied with measuring the water contact angle. Cell adhesion and morphology was assessed from images taken with scanning electron microscopy, whereas cell viability was measured with a calorimetric assay. The obtained results showed that oxygen plasma treatment of TiO2 nanotube surfaces significantly influences the adhesion and morphology of osteoblast-like cells in comparison to untreated nanostructured surfaces. Marked changes in surface composition of plasma treated surfaces were observed, as plasma treatment removed hydrocarbon contamination and removed fluorine impurities, which were present due to the electrochemical anodization process. However no differences in wettability of untreated and plasma treated surfaces were noticed. Treatment with oxygen plasma stimulated osteoblast-like cell adhesion and spreading on the nanostructured surface, suggesting the possible use of oxygen plasma surface treatment to enhance osteoblast-like cell response.